CLASSIFICATION ANALYSIS OF HOTS LOTS ON EVALUATION OF STUDENT WORKSHEETS (LKS) OF ARABIC SUBJECT AT MADRASAH TSANAWIYAH 8 th GRADE - Nurul Fadilah; Muflihah Muflihah (AL LUGHAH, 2022)
Each classroom learning requires evaluation activities to assess students' competence and understanding after learning. The test instrument is one tool to measure this. Because each student is required to be critical in order to achieve optimal learning. So the existence of Bloom's cognitive category appears to determine which questions are provided for which scope and purpose. This study aims to analyze how many questions require high thinking. So that educators know which questions require low and high levels of thinking from the LKS.